NEW STYLE OF THE CULTURAL HERITAGE - N. M. Mamedova (Научный вестник МГТУ ГА, 2016)
The paper analyzes the characteristics of the broadcast of sociocultural experience. It is shown that modern historical stage is associated with the formation of a united democratic style of relationship to the cultural heritage of the past. It is caused by deep-seated patterns of culture itself, increased integration in all spheres of society. In this regard, feature of temporal being culture - the presence of social memory is highlighted. Formation of human values is the result of a kind of cultural history. As a key mechanism of successive development of a culture increasingly recognized the need for careful and responsible attitude to national cultures, to the cultural wealth of mankind.